IMPLEMENTASI PASAL 41 UNDANG-UNDANG PERKAWINAN TENTANG PEMENUHAN HAK-HAK ANAK PASCA PERCERAIAN BERDASARKAN PERSPEKTIF HUKUM ISLAM (STUDI KASUS PENGADILAN AGAMA SINGARAJA) - Deni Rosadi; Ketut Sudiatmaka; Muhamad Jodi Setianto (Jurnal Ilmu Hukum Sui Generis, 2023)
This research aims to find out and analyze the implementation of Article 41 of the Marriage Law concerning the Fulfillment of Children's Rights After Divorce Based on an Islamic Law Perspective in Buleleng Regency. The type of research used in this research is empirical juridical. This research is descriptive qualitative in nature. The location of this research is the Singaraja Religious Court. The type of research used is empirical legal research and this research is descriptive. The data collection techniques used are observation techniques, interview techniques and document study techniques. The research sampling technique used was purposive sumpling. The results of the research show that the factors causing divorce are child marriage factors which are caused by economic factors and communication and mental health. Fulfillment of children's rights as a result of parental divorce in the jurisdiction of the Singaraja Religious Court has not yet gone completely well. This is because most ex-husbands, after officially divorcing, no longer carry out their obligations as fathers who have the responsibility to provide support for their children. Apart from that, most married couples in the jurisdiction of the Singaraja Religious Court divorce because there are economic problems in their families. In giving a decision regarding the provision of children's rights after divorce, the Singaraja Religious Court Judge was in accordance with Article 41 of the Marriage Law concerning the Fulfillment of Post-Divorce Rights.